1991
DOI: 10.1128/mcb.11.12.6034
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian stress proteins HSP70 and HSP28 coinduced by nicotine and either ethanol or heat.

Abstract: Cells exposed to a variety of stresses such as heat or ethanol respond by increasing their rate of synthesis of a set of proteins termed heat shock proteins (HSP). These proteins then appear to offer protection against the stressor and many other insults. The HSP also play important roles in unstressed cells. They are involved in the regulation of the cell cycle and during specific stages in the development of organisms. Exposure to stress during development (e.g., in pupal stages of insects or during gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…Alteration of heat shock protein production, inhibition of cell metabolism and proliferation and induction of nuclear aberrations are some of the common results of smokeless tobacco extract and nicotine administration (Hahn et al 1991;Doolittle et al 1995;Trivedi et al 1990;Tipton et al 1995;Konno et al 1991;Lee et al 1996.). In addition, it has been demonstrated that both nicotine and smokeless tobacco administration results in generation of reactive oxygen species during in vitro experimental systems (Ashakumary et al 1996;Bagchi et al 1995).…”
mentioning
confidence: 96%
“…Alteration of heat shock protein production, inhibition of cell metabolism and proliferation and induction of nuclear aberrations are some of the common results of smokeless tobacco extract and nicotine administration (Hahn et al 1991;Doolittle et al 1995;Trivedi et al 1990;Tipton et al 1995;Konno et al 1991;Lee et al 1996.). In addition, it has been demonstrated that both nicotine and smokeless tobacco administration results in generation of reactive oxygen species during in vitro experimental systems (Ashakumary et al 1996;Bagchi et al 1995).…”
mentioning
confidence: 96%
“…Alteration of heat shock protein production Hahn et al 1991), inhibition of cell metabolism and proliferation (Konno et al 1991;Waggoner and Wang 1994), and induction of nuclear aberrations (Livingstone et al 1990;Doolittle et al 1995) are some of the common results of smokeless tobacco extract and nicotine administration. In addition, it has been demonstrated that both nicotine and smokeless tobacco administration result in generation of reactive oxygen species in in vitro experimental systems Wetscher et al 1995a).…”
mentioning
confidence: 99%
“…There are examples of such synergy in mammalian (6,8,(13)(14)(15), fungal (4), and amphibian (7) cells. In four cases, this synergy is at the level of mRNA synthesis (4,7,14,15), suggesting transcriptional control.…”
mentioning
confidence: 99%